IBM System p5 Approaches to 24x7 Availability Including AIX 5L - Blanchard, Bruno (Ibm.com/Redbooks, 2006)
This IBM® Redbook focuses on the IBM System p server. It describes the technology, serviceability, and features that are used by the IBM System p5 servers, which allow you to make your server one of the most reliable and available parts of your IT infrastructure. This redbook explains how server availability can be improved by: Planning of the complete server environment and configuration; Understanding the role of the service processors and firmware components, and how they can be best configured and managed; Using high availability and redundancy features provided by the AIX® 5L operating system and the Virtual I/O Server. -- from preface.
Includes bibliographical references and index
Keywords: Client/server computing; Information technology; IBM System p5; Architecture client-serveur (Informatique); Technologie de l'information; information technology